A Neutrosophic Eco-Dynamical Framework for Rural Ecotourism Management Quality under Urban Expansion Pressure - Hongxia Lei; Hongxia Lei (Neutrosophic Sets and Systems)
This paper introduces a novel neutrosophic mathematical model for managing rural ecotourism quality under the growing influence of urban development. Traditional planning approaches fail to capture the interplay between sustainability, uncertainty, and degradation in fragile rural ecosystems. We propose the Neutrosophic Eco-Dynamical Lattice (NEDL), a spatial-temporal model where each region is represented by a truth– indeterminacy–falsehood triplet, evolving over time. Through systems of partial differential equations, neighbor interactions, and recovery dynamics, the model reflects how tourism pressure and urban encroachment impact land quality. A complete 4×4 case study demonstrates how truth (ecological health) declines, uncertainty rises, and collapse conditions emerge. Based on simulation results, we introduce a neutrosophic zoning strategy, triplet-based early warning system, and recovery prioritization. This study offers a new planning paradigm, rooted in neutrosophic reasoning, for sustainable rural ecotourism management.